Análise multivariada das atividades científicas e técnicas no processo de adoção de inovação em empresas sucroenergéticas do centro-oeste do estado de São Paulo - Lampkowski, Francisco José [UNESP]; Biaggioni, Marco Antônio Martin [UNESP] (EIA Energy in Agriculture, 2013)
The primary objective of this study was to verify the existence of internal organization and processes influencing the decisions on adoption, choice, justification and implementation of innovative practices of scientific and technical activities undertaken in the elaborates of sugar, ethanol and energy companies of the midwest of the state of Sao Paulo. Using multivariate analysis of principal components and clusters, the variables were analyzed and the companies, classified. The taxonomy model adapted to contemporary situations described by Freeman (1975), was the 'parameter used with research information in personal interviews by semi-structured questionnaires. The investigated activities constituted of: basic research; applied research; experimental development; scientific and technical information; long-term planning. The variables analyzed were: production processes, operating systems, development of new products, projects and implementation of pilot plant for new products, development, knowledge, studies of other business segments, number of innovations, and the number of existing employees in the organizational structure for these purposes. It was concluded that the best companies with innovative attitudes are those that have incorporated into their organizational the structures, practices and techniques of scientific activities.

O objetivo principal foi verificar a existência de organização e de processos internos influenciando a questão decisória na adoção, escolha, justificativa e implementação de inovação pelas práticas de atividades científicas e técnicas desenvolvidas nas empresas sucroenergéticas do centro-oeste do estado de São Paulo. Utilizando-se de análise multivariada de componentes principais e de agrupamentos, as variáveis foram analisadas e as empresas classificadas. Adaptado às situações contemporâneas, o modelo de taxionomias de Freeman (1975), foi o parâmetro, com informações pesquisadas em entrevistas diretas por questionários semi-estruturados. Constituíram as atividades investigadas: pesquisa básica; pesquisa aplicada; desenvolvimento experimental; informações científicas e técnicas; planejamento de longo prazo. Em cada atividade as variáveis abordadas foram: nos processos de produção; sistemas operacionais; desenvolvimento de novos produtos; projetos e implementação de planta piloto para novos produtos; desenvolvimento, conhecimento, estudos de outros segmentos de negócios; número de inovações; número de funcionários existentes na estrutura de organização para estas finalidades. Concluiu-se que as melhores empresas com posturas inovadoras são aquelas que têm incorporadas em suas estruturas de organização as práticas de atividades científicas e técnicas.
Multivariate analysys of scientific and technical activities in the process of adoption of innovation in companies of the sugar, ethanol and energy of midwest of the state of São Paulo
Keywords: Innovation; Technology; Scientific; Sugar; Ethanol and energy; Companies; Inovação; Tecnologia; Atividades científicas; Empresas sucroenergéticas